2015
DOI: 10.15252/embj.201489966
|View full text |Cite
|
Sign up to set email alerts
|

Commensal microbiota influence systemic autoimmune responses

Abstract: Antinuclear antibodies are a hallmark feature of generalized autoimmune diseases, including systemic lupus erythematosus and systemic sclerosis. However, the processes underlying the loss of tolerance against nuclear self-constituents remain largely unresolved. Using mice deficient in lymphotoxin and Hox11, we report that approximately 25% of mice lacking secondary lymphoid organs spontaneously develop specific antinuclear antibodies. Interestingly, we find this phenotype is not caused by a defect in central t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 37 publications
1
58
0
2
Order By: Relevance
“…Another example of a pronounced immune-modulatory function of the microbiota is the ability of segmented filamentous bacteria (SFB) to direct the immune system of mice towards increased production of T H 17 cells, thereby protecting the animals from infectious agents 55 . Our research group also showed that SFB present during the neonatal colonization process in mice are important microbial components in the development of systemic autoimmunity in adult life 56 .…”
Section: Regulation Of Intestinal Immunitymentioning
confidence: 64%
See 4 more Smart Citations
“…Another example of a pronounced immune-modulatory function of the microbiota is the ability of segmented filamentous bacteria (SFB) to direct the immune system of mice towards increased production of T H 17 cells, thereby protecting the animals from infectious agents 55 . Our research group also showed that SFB present during the neonatal colonization process in mice are important microbial components in the development of systemic autoimmunity in adult life 56 .…”
Section: Regulation Of Intestinal Immunitymentioning
confidence: 64%
“…2). This depletion ablates formation of isolated lymphoid follicles, along with an expansion of SFB 56 . Similarly, the secretion of lymphotoxin by intestinal innate lymphoid cells has been shown to regulate the production of IgA and microbiota composition in the gut of adult animals 147 , as does TLR5 or NLRP6 deficiency in mice 148,149 .…”
Section: Other Rheumatic Diseasesmentioning
confidence: 96%
See 3 more Smart Citations